2014
DOI: 10.1093/eurheartj/ehu112
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide experience with a totally subcutaneous implantable defibrillator: early results from the EFFORTLESS S-ICD Registry

Abstract: AimsThe totally subcutaneous implantable-defibrillator (S-ICD) is a new alternative to the conventional transvenous ICD system to minimize intravascular lead complications. There are limited data describing the long-term performance of the S-ICD. This paper presents the first large international patient population collected as part of the EFFORTLESS S-ICD Registry.Methods and resultsThe EFFORTLESS S-ICD Registry is a non-randomized, standard of care, multicentre Registry designed to collect long-term, system-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
359
6
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 434 publications
(402 citation statements)
references
References 38 publications
21
359
6
16
Order By: Relevance
“…In contrast to the development of transvenous ICDs 20 to 30 years ago, step‐down defibrillation threshold (DFT) testing was rarely performed. In the largest S‐ICD registry to date, only 10 of 450 patients had any testing done at <65 J 6, 7…”
mentioning
confidence: 99%
“…In contrast to the development of transvenous ICDs 20 to 30 years ago, step‐down defibrillation threshold (DFT) testing was rarely performed. In the largest S‐ICD registry to date, only 10 of 450 patients had any testing done at <65 J 6, 7…”
mentioning
confidence: 99%
“…On the other hand, as the leads are extracardiac, the sensing and programing differ from that of the TV‐ICD, posing new challenges. The 360‐day rate of IASs observed in the EFFORTLESS S‐ICD Registry was 7% 5. Supraventricular tachycardias account for the majority of IASs associated with TV‐ICDs, whereas oversensing, especially TWOS, is the primary cause of IASs associated with S‐ICDs 2, 4, 5, 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of IASs are due to T‐wave oversensing (TWOS), which has been reduced by exercise testing 4, 5. Here, we report the case of a patient who experienced an IAS due to TWOS, which a prior exercise test could not predict.…”
Section: Introductionmentioning
confidence: 96%
“…In subsequent S-ICD studies, premature battery depletion was observed in 2 cases (0.6%) in the IDE trial and in 1 case (0.2%) in the EFFORTLESS registry. 14,15 When considering transvenous ICD systems, premature ERI has been reported in 9% of transvenous devices. 21 Battery malfunctions were the most common cause of device failure in a meta-analysis of device registries.…”
Section: Discussionmentioning
confidence: 99%
“…The interim analysis of the EFFORTLESS registry reported a low explant rate of the S-ICD, occurring in 3.7% of patients mainly because of infection. 15 In 1% of patients, the S-ICD was replaced for a transvenous ICD system because of recurrent ventricular arrhythmias or patient decision.…”
Section: Discussionmentioning
confidence: 99%